Influence of the Ripening Stage and Extraction Conditions on the Phenolic Fingerprint of 'Corbella' Extra-Virgin Olive Oil - Anallely López-Yerena; Antonia Ninot; Núria Jiménez-Ruiz; Julián Lozano-Castellón; Maria Pérez; Elvira Escribano-Ferrer; Agustí Romero-Aroca; Rosa M. Lamuela-Raventós; Anna Vallverdú-Queralt (MDPI AG, 2021)
The ancient 'Corbella' olive variety from the center-north of Catalonia is being recovered to obtain quality extra-virgin olive oil (EVOO) with unique organoleptic properties. The aim of this work was to determine the effect of agronomic and technical factors on the phenolic fingerprint of EVOO and to establish the optimum harvesting time and crushing and malaxation conditions for 'Corbella' olives. Therefore, three different ripening indices (0.3, 1.2, and 3.2) and three crushing temperatures (10, 18, and 25 OC) were studied. Additionally, a factorial design to optimize the phenolic concentration of the EVOO was developed, applying a range of sieve diameters (4 and 6 mm), and malaxation time (30 and 60 min) and temperature (27, 32, and 37 °C). The phenolic profile was analyzed by ultra-high performance liquid chromatography coupled to mass spectrometry in a tandem detector. The level of secoiridoids, the major phenolic compounds in the oil, was higher when using olives harvested earlier. Oleuropein aglycone and ligstroside aglycone were degraded during crushing at high temperatures, resulting in the formation of oleacein and oleocanthal. The best processing conditions in terms of total phenolic content were found to be 30 min of malaxation at 37 OC, the crushing size not having any affect.